дайте ответ правильный, (3x-1/2)2=3x×2-0,5×2=6x-1

(5y+1/5)2=5y×2+1/5×2=10y+2/5

(-6x-5)2=-6x×2-5×2=-12x-10

(-7x-2)2=-7x×2-2×2=-14x-4

(X3-3y)2=(3x-3y)2=6x-6y

(5y-x3)2=(5y-3x)2=10y-6x

(7x+y4)2=(7x+4y)2=14x+8y

(X5-8y)2=(5x-8y)2=10x-16y

100132 100132    2   15.01.2021 08:31    0

Ответы
Daina1115 Daina1115  15.01.2021 08:40

(3*-1/2)2=3*2-0,5*2=6x-1 (5y+1/5)2=5y*2+1/5*2=10y+2/5 (-6x-5)2=-6*2-5*2=-12*-10 (-7x-2)2=-7**2-2*2=-14x-4 (x3-3y)2=(3x-3y)2=6x-6y (5y-x3)2=(5y-3x)2=10y-6x (7x+y4)2=(7x+4y)2=14x+8y (x5-8y)2=(5x-8y)2=10x-16y

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра